Разновозрастное спаривание как механизм регулирования численности популяции - Граков, Н.Н. (Вестник зоологии, 1980)
Analysis of the author’s own data and those from literature shows the presence of different-age mating in some species of mammals, which results in predominance of males or females in the progeny. Age crossing is ensured by peculiarities of intrapopulation location of specimens and non-simultaneous puberty of males and females.